Treatment with an AMPA antagonist 12 hours following severe normothermic forebrain ischemia prevents CA1 neuronal injury. - Li, H; Buchan, A (1993)
The neuroprotective effects of 2,3-dihydroxy-6-nitro-7- sulfamoylbenzo(f)quinoxaline (NBQX), GYKI 52466, and MK-801 were tested following severe forebrain ischemia. Wistar rats were subjected to 10 min of normothermic ischemia and reperfused for 7 days. Necrotic hippocampal CA1 neurons were counted and expressed as a percentage (mean +/- SD). In Experiment 1, saline-treated rats sustained 81 +/- 20% damage to dorsal CA1. Rats given NBQX 30 mg/kg i.p. x3 lost 21 +/- 27% (p < 0.01). Neither MK-801 1 mg i.p. x3 alone, nor in combination with the cytoprotective dose of NBQX protected CA1, with 83 +/- 18 and 54 +/- 34% damage, respectively (NS). Giving NBQX 90 mg/kg i.v. did not protect cells (94 +/- 5%) and resulted in nephrotoxicity. In Experiment 2, rats were given saline or three doses of NBQX 30 mg/kg i.p. immediately at reperfusion (RP) or after a 6-, 12-, or 24-h delay. Saline-treated rats suffered 79 +/- 16% injury. NBQX given immediately resulted in 17 +/- 17% injury, and even if treatment was delayed by either 6 or 12 h, there was marked protection with only 27 +/- 32 and 25 +/- 17% injury, respectively (all p < 0.01). Delaying the initiation of treatment to 24 h was not successful, resulting in 50 +/- 28% injury (NS). In Experiment 3, saline-treated rats lost 81 +/- 19% of CA1 cells, while those given GYKI 52466 10 mg/kg i.p. x5 starting immediately following RP lost 80 +/- 14%.(ABSTRACT TRUNCATED AT 250 WORDS)